EVALUATION OF THE QUALITY OF THE RIO VERDE WATER, PONTA GROSSA, PR: A STUDY ON THE CONDITIONS OF AQUATIC LIFE MAINTENANCE AND THE EUTROPHICATION PROCESS - Costa, Karine Andréa; Scheffer, Elizabeth Weinhardt Oliveira; Weinert, Patrícia Los; Silveira, Estevan Luis (Eclética Química, 2018)
The objective of this work was to evaluate the physicochemical parameters that express the water quality of the Rio Verde, in the city of Ponta Grossa, Paraná. Multivariate Analysis was used, and quality indexes were obtained, such as the Trophic State Index and the Water Quality Index for Aquatic Life Protection. River samples were collected at 4 points along the Rio Verde for 12 months. The study showed that the river presents a high trophic degree, and that it can be considered hypereutrophic, and that phosphorus concentration is determinant for this situation. The results indicated that, at point 4, downstream from the Sewage Treatment Plant, the aquatic environment is very poor for the biota. The disposal of the effluent was indicated as the cause, and it is assumed that the river has no flow capacity to receive this contribution, without suffering impact. It was also concluded that points 1 and 2 correspond to more preserved sites, but are not totally favorable to aquatic life either because they receive surface drainage from agricultural areas in the basin. Point 3, of urban character, suffers an impact caused by irregular connections of sewers, and contribution of streams that flow into the river.